Employee Burnout dan Organizational Commitment terhadap Job Satisfaction dengan Organizational Citizenship Behavior - Josephine Justina; Hery Winoto Tj; Melitina Tecoalu (Journal of Management and Bussines (JOMB), 2022)
This study aims to see the effect of employee burnout and organizational commitment on job satisfaction mediated by organizational citizenship behavior. This research method is quantitative with a total sample of 62 employees taken from a total of 119 Jubilee School employees. Data were obtained through electronic questionnaires that were digitally administered to respondents. The analysis technique used is Partial Least Square - Structural Equation Modeling (PLS-SEM) using the SmartPLS program. The results showed that there was a significant effect for employee burnout and organizational commitment on job satisfaction but organizational citizenship behavior did not mediate the effect of employee burnout and organizational commitment on job satisfaction. From the results of this study it was found that organizational commitment had a significant positive effect on job satisfaction, employee burnout had a significant negative effect on job satisfaction. In conclusion, Jubilee schools need to pay attention to the level of commitment and mental health of employees and teachers so that the level of job satisfaction is maintained. Jubilee Schools also need to establish emotional relationships with employees and teachers so that organizational citizenship behavior is really carried out for the good of the school and not just for the benefit of students. Keywords: Employee Burnout, Citizenship Behavior, Organizational Commitment, Organizational Job Satisfaction